The Role of Plastic Recycling Shops in Khulna City Within A Circular Economy Framework (Journal of Engineering Science, 2024)
Plastics are widely used in many industries, leading to a growing plastic waste problem. To address this, a shift from a linear economy to a circular economy is required. In Bangladesh, the waste management sector predominantly relies on the informal sector, which remains underappreciated and inadequately supported. This study evaluates the environmental, economic, social, and urban development dimensions of recycling shops within the informal sector, highlighting their potential to alleviate ecological burdens, enhance energy efficiency, and generate local employment. A comprehensive methodology encompassing field surveys, environmental and economic benefit calculations, and fuzzy logic analysis are employed. The findings demonstrate that recycling shops, through a circular economy approach, substantially mitigate greenhouse gas emissions, reduce litter, save energy, and conserve landfill space. Among the 35 recycling shops examined, 22.86% were identified as low-volume recyclers, 48.57% as medium-volume recyclers, and 28.57% as high-volume recyclers, each group exerting correspondingly low, medium, and high positive impacts on the environment and society. Collectively, these shops manage 6.68 tons of PET bottle labels, reduce greenhouse gas emissions by 509.35 MTCE, prevent 202,186.9 tons of litter, save 5,728.1 m³ of landfill space, and conserve 406.8 barrels of oil monthly. Additionally, they employ 427 individuals. Expanding recycling shop operations, exploring new recycling technologies, and examining supportive policies are crucial for improving Khulna City's plastic waste management and overall sustainability.Journal of Engineering Science 15(1), 2024, 31-43